Persistent air-leak after transhiatal oesophagectomy: A case report - Khan, Mashuk A. (Elsevier, 2013)
INTRODUCTION: Transhiatal oesophagectomy is a widely accepted technique for resection of tumours of the lower oesophagus. We present a life-threatening complication associated with the placement of a corrugated neck drain during this procedure. PRESENTATION OF CASE: Our patient underwent a transhiatal oesophagectomy for a lower oesophageal tumour. He developed persistent bilateral pneumothoraces despite chest drain insertions. Following removal of the corrugated neck drain, both lungs were successfully re-inflated. DISCUSSION: To the authors’ knowledge, this serious complication has been described only once before in the medical literature; other surgeons should be made aware of this problem. CONCLUSION: Alternative drainage systems should be considered to help prevent this injury. Exercise caution if positioning corrugated drains in the neck.